2022
DOI: 10.1021/acsmaterialslett.2c01020
|View full text |Cite
|
Sign up to set email alerts
|

External Heavy-Atom Activated Phosphorescence of Organic Luminophores in a Rigid Fluid Matrix

Abstract: Growing attention has been paid to pure organic room-temperature phosphorescence (RTP). Although an insufficient population and fast nonradiative decay of triplet excitons are avoided in recent endeavors, complicated synthesis and limited universality still hinder its development. Further, fluid RTP materials are more difficult to design because of faster nonradiative relaxation. Herein, a deep eutectic mixture of glucose and choline, a stable supercooled liquid at room temperature, is employed as a matrix. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 52 publications
(61 reference statements)
2
19
0
Order By: Relevance
“…As for the delayed emission spectrum, the 441 band is completely wiped off, indicating that it is probably a fluorescent state (S 1 ) and the band at room temperature is from thermally activated delayed fluorescence (TADF). [28] To further confirm the conclusion from PL spectra, the luminescence lifetimes of each band were measured at both RT and 77 K. At RT, we found that the fitted lifetime collected at 441 nm has two components, i.e., τ 1 = 1.26 ns and τ 2 = 80.6 ms (Figure S58). At 77 K, a single component of τ 1 = 1.81 ns is present, which clearly points to the TADF mechanism.…”
Section: Resultssupporting
confidence: 53%
“…As for the delayed emission spectrum, the 441 band is completely wiped off, indicating that it is probably a fluorescent state (S 1 ) and the band at room temperature is from thermally activated delayed fluorescence (TADF). [28] To further confirm the conclusion from PL spectra, the luminescence lifetimes of each band were measured at both RT and 77 K. At RT, we found that the fitted lifetime collected at 441 nm has two components, i.e., τ 1 = 1.26 ns and τ 2 = 80.6 ms (Figure S58). At 77 K, a single component of τ 1 = 1.81 ns is present, which clearly points to the TADF mechanism.…”
Section: Resultssupporting
confidence: 53%
“…However, this does not conform to the conventional principle of heavy atom-enhanced phosphorescence. [51][52][53] Therefore, this further proves the confinement contribution of the inorganic matrix to RTP. The doping of metal ions will affect the change of the inorganic matrix lattice, as confirmed by XRD (Figure 6F and Figure S29).…”
Section: Angewandte Chemiesupporting
confidence: 61%
“…The phosphorescence lifetime is also gradually reduced (Figure S28 and Table S4). However, this does not conform to the conventional principle of heavy atom‐enhanced phosphorescence [51–53] . Therefore, this further proves the confinement contribution of the inorganic matrix to RTP.…”
Section: Resultsmentioning
confidence: 79%
“…Ma and Tian et al 44 used a kind of deep eutectic supramolecular polymer (DESP) to prepare supramolecular polymer-based RTP materials (Figure 5b). The transparent DESP 45 was made of hydrogen bonding interaction by using βcyclodextrin as hydrogen bond acceptor and natural organic small molecule acid (malic acid or citric acid) as hydrogen bond donor. The network is rich in hydrogen bonds, making it high viscosity and flowability, which is beneficial for promoting RTP.…”
Section: Supramolecular Polymersmentioning
confidence: 99%